Lever Assy Product Distribution Needs Planning with the Distribution Requirement Planning Method in the Automotive Industry - Herdiana, Mochamad Rafi; Herwanto, Dene (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
The market demand to get quality products is not enough to be answered only by the company's ability to provide the requested products, the company's ability to fulfill order stock, low prices, order time targets, and marketing capabilities. Planning for product availability and distribution processes is also needed to meet consumer needs. PT XYZ is a company engaged in the automotive sector as a supplier. The problem that occurs is that there is an over cost distribution so that the company has to increase costs for the distribution of Lever Assy products. One of the reasons that allegedly caused the problem was because the forecasting that became the basis for the company to take policies in the distribution process of the Lever Assy product was not done properly. The goal to be achieved in this study is to plan distribution needs by considering the demand aspect to avoid over cost distribution. The results of this study show that the total cost incurred based on the company method is Rp71,614,500, while using the distribution requirement planning method is Rp52,864,500, which means that there is a savings of Rp.18,750,000 with a percentage of 26%.